THE ROLE OF ISLAMIC RELIGIOUS EDUCATION IN THE FORMATION OF INCLUSIVE CHARACTER: A PHENOMENOLOGICAL STUDY OF MULTICULTURAL SOCIETIES IN INDONESIA - Berly Wijayanti; Mokhammad Khosim; Satuyar Mufid; Alvin Dian Pramuja (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
Islamic Religious Education has a strategic role in shaping the character of students who are not only religious, but also inclusive in facing the realities of a multicultural society. The diversity of religions, cultures, and backgrounds of the people in Indonesia requires Islamic Religious Education to provide guidance on the values of tolerance, moderation, and respect for differences, especially in the field of education. This study aims to understand the role of Islamic Religious Education in shaping inclusive character through a phenomenological approach. The research was conducted in the context of Islamic religious education in multicultural communities in Indonesia, emphasizing the meaning of the experience of inclusivity values in the practice of Islami Religious Education. The phenomenological approach was used to explore the meaning of subjective experiences related to the internalization of the values of justice, compassion, empathy, and social responsibility. The results of the analysis show that Islamic Religious Education is understood not only as a process of imparting religious knowledge, but as a space for the formation of human consciousness that encourages openness, mutual respect, and harmonious coexistence. These findings confirm that Islamic Religious Education plays an important role as an instrument for inclusive character building and strengthening social cohesion in Indonesia's multicultural society.